Biomass and species composition of green macroalgae in the Binhai Harbor intertidal zone of the Southern Yellow Sea. (January 2023) - Xia, Zhangyi; Yuan, Huanqing; Liu, Jinlin; Zhao, Shuang; Tong, Yichao; Sun, Yuqing; Li, Shuang; Li, Aiqin; Cao, Jiaxing; Xia, Jing; Dai, Wei; Zhang, Jianheng; et al.
Abstract: Green tides have occurred in the Southern Yellow Sea (SYS) for 16 consecutive years, causing widespread concern. Attached and floating green macroalgae have been observed in Binhai Harbor, Jiangsu Province, China, in the SYS. This study used morphological analysis, and internal transcribed spacers and rps2- trn L molecular identification methods, to analyze the species composition and biomass of green macroalgae along the Binhai Harbor coast. Six species of green tide algae ( Ulva prolifera, Ulva meridionalis, Ulva linza, Ulva flexuosa, Ulva californica, and Ulva intestinalis ) were identified, in addition to Blidingia sp. The discovery of U. californica is the first report of this species off the coast of Jiangsu Province. The floating green macroalgae along the Binhai Harbor coast originated from attached green macroalgae in Binhai Harbor, and a small number of the attached algae were closely related to the large-scale floating U. prolifera in the SYS. Moreover, in December 2021, February 2022, and April 2022, the total biomass of attached green macroalgae in Binhai Harbor was 25.600, 10.767, and 25.867 t, respectively, of which the U. prolifera biomass was 10.697, 8.709, and 4.185 t, respectively. This study proved Binhai Harbor may not be an important source of green tide in the SYS. Highlights: Six species of Ulva were found in Binhai Harbor. Ulva californica, usually in the Eastern Pacific, now appears in the Yellow Sea. Floating macroalgae near Binhai Harbor are derived from attached algae in the harbor. Binhai Harbor may not be a major source of green tides in the Southern Yellow Sea.